Arranged' marriage, co-residence and female schooling: a model with evidence from India - Indraneel Dasgupta; Pushkar Maitra; Diganta Mukherjee (Institute for the Study of Labor (IZA), 2008)
We model the consequences of parental control over choice of wives for sons, for parental incentives to educate daughters, when the marriage market exhibits competitive dowry payments and altruistic but paternalistic parents benefit from having married sons live with them. By choosing uneducated brides, some parents can prevent costly household partition. Paternalistic self-interest consequently generates low levels of female schooling in the steady state equilibrium. State payments to parents for educating daughters fail to raise female schooling levels. Policies (such as housing subsidies) that promote nuclear families, interventions against early marriages, and state support to couples who marry against parental wishes, are however all likely to improve female schooling. We offer evidence from India consistent with our theoretical analysis.
Keywords: D10; 300; Arranged marriage; dowry; bride price; female literacy; marriage markets; stable marriage allocation; Frauenbildung; Ehe; Eltern; Entscheidung; Familienökonomik; Wohnsoziologie; Theorie; Indien